The Irony of Judicial Elections - David E. Pozen (My University, 2016)
Judicial elections in the United States have undergone a dramatictransformation. For more than a century, these state and local elections wererelatively dignified, low-key affairs. Campaigning was minimal; incumbentsalmost always won; few people voted or cared. Over the past quarter centuryand especially the past decade, however, a rise in campaign spending, interestgroup involvement, and political speech has disturbed the traditional paradigm.In the “new era,” as commentators have dubbed it, judicial racesroutinely feature intense competition, broad public participation, and highsalience.This Article takes the new era as an opportunity to advance our understandingof elective versus nonelective judiciaries. In revisiting this classicdebate, the Article aims to make three main contributions. First, it offers ananalytic taxonomy of the arguments for and against electing judges thatseeks to distinguish the central normative concerns from the more contingent,empirical ones. Second, applying this taxonomy, the Article shows how boththe costs and the benefits of elective judiciaries have been enhanced by recentdevelopments, leaving the two sides of the debate further apart than ever.Finally, the Article explores several deep ironies that emerge from thiscleavage. Underlying these ironies is a common insight: As judicial electionsachieve greater legitimacy as elections, they will increasingly underminethe judiciary’s distinctive role and our broader democratic processes. There isan underappreciated tradeoff between the health of judicial elections and thehealth of the judiciary, the Article posits, that can help recast the controversyover the new era.Judicial elections in the United States have undergone a dramatictransformation. For more than a century, these state and local elections wererelatively dignified, low-key affairs. Campaigning was minimal; incumbentsalmost always won; few people voted or cared. Over the past quarter centuryand especially the past decade, however, a rise in campaign spending, interestgroup involvement, and political speech has disturbed the traditional paradigm.In the “new era,” as commentators have dubbed it, judicial racesroutinely feature intense competition, broad public participation, and highsalience.  This Article takes the new era as an opportunity to advance our understandingof elective versus nonelective judiciaries. In revisiting this classicdebate, the Article aims to make three main contributions. First, it offers ananalytic taxonomy of the arguments for and against electing judges thatseeks to distinguish the central normative concerns from the more contingent,empirical ones. Second, applying this taxonomy, the Article shows how boththe costs and the benefits of elective judiciaries have been enhanced by recentdevelopments, leaving the two sides of the debate further apart than ever. Finally, the Article explores several deep ironies that emerge from thiscleavage. Underlying these ironies is a common insight: As judicial electionsachieve greater legitimacy as elections, they will increasingly underminethe judiciary’s distinctive role and our broader democratic processes. There isan underappreciated tradeoff between the health of judicial elections and thehealth of the judiciary, the Article posits, that can help recast the controversyover the new era.